AN ANALYSIS OF CLASSROOM MANAGEMENT DIFFICULTIES IN THEMATIC LEARNING IN SD N 2 KUTOSARI - Ana Nur Fajriyati; Mutiara Anggun Puspitasari (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
Curriculum 2013 has started to be implemented in schools, including in SD N 2 Kutosari. One of its realizations is the thematic learning for grade 1, 2, 4, and 5. The implementation needs a good classroom management in order to achieve maximum learning objectives. However, in the actual act, there are still teachers who have difficulties in managing the classroom for the thematic learning. The purpose of this research was to describe problems in the classroom management for the thematic learning in SD N 2 Kutosari. The approach used in this research was qualitative with descriptive analysis. The data were collected through observation, documentation, and interview to the teachers. Result showed that there are problems, such as (1) Students feltbored easily to the learning subject (2) Students were busy talking with their friends (3) Students were busy to get attention from the teachers and the other students (4) The number of students in class exceeded the ideal number (5) Students tended to choose friends in group discussion (6) Less interesting subject (7) A static classroom setting.